2023
DOI: 10.1039/d3ta00519d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of angular-shaped naphthodithiophenediimide and its donor–acceptor copolymers as nonvolatile polymer additives for organic solar cells

Abstract: Naphthalenediimide (NDI) and its pi-extended derivatives have been one of the most important building blocks to constitute n-type organic semiconductors. To further explore new materials in the NDI family, an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…1c). 97 According to the PL spectra results, introducing PBM or PFBM into the PM6:Y6 blended film increased the quenching efficiency, indicating the enhanced intermolecular charge transfer. The GIWAXS and AFM results suggested that PBM and PFBM improved the crystallinity of Y6 and reduced side-chain interdigitation lamellar spacing of PM6, which was conducive to charge carrier transport, accounting for the increased J SC and FF (Table 4).…”
Section: Solid Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…1c). 97 According to the PL spectra results, introducing PBM or PFBM into the PM6:Y6 blended film increased the quenching efficiency, indicating the enhanced intermolecular charge transfer. The GIWAXS and AFM results suggested that PBM and PFBM improved the crystallinity of Y6 and reduced side-chain interdigitation lamellar spacing of PM6, which was conducive to charge carrier transport, accounting for the increased J SC and FF (Table 4).…”
Section: Solid Additivesmentioning
confidence: 99%
“…Polymer donors and small molecular acceptors with appropriate miscibility, complementary absorption and compatible energy levels were also used as nonvolatile solid additives. [97][98][99][100][101][102][103] Cheng et al enhanced the PCE of PM6:Y6 based OSCs by utilizing two polymers PBM and PFBM as additives (Fig. 1c).…”
Section: Nonvolatile Solid Additivesmentioning
confidence: 99%
“…In order to push the PCE of PM6:Y6 OPVs to a new level, the additive strategy, solvent strategy, transport layer strategy, , and ternary strategy , have been studied. Among them, the ternary strategy is one of the most effective and convenient ways .…”
Section: Introductionmentioning
confidence: 99%
“…1 Modification of classic A units 8–16 [ e.g. , naphthalene diimide (NDI) and perylene diimide (PDI)] or the creation of novel A systems, 17–26 therefore, has recently become a popular subject of engineering the optoelectronic properties of CPSs.…”
Section: Introductionmentioning
confidence: 99%